Analysis of Determinants of Maternal Mortality due to Obstetric Complications at Dr. M. Djamil Padang Hospital in 2017 - 2020 - Farah Tri Ulfa; Yusrawati Yusrawati; Dedy Kurnia (International Journal of Medicine and Health, 2024)
Maternal mortality is one of the unresolved health problems in the world. Obstetric complications directly in maternal mortality (pregnancy complications, childbirth, and the puerperium). This study aims to analyze the relationship between the determinants of maternal mortality due to obstetric complications. This type of research is an observational analytic study with a case-control design. In this study, there were 48 case samples and 144 control samples with a ratio of 1:3. The data obtained in the form of patient medical record data. Data analysised by univariate, bivariate and multivariate. The results showed that the most common cause of maternal death was preeclampsia/eclampsia. Risk factors that have a significant relationship with maternal mortality due to obstetric complications are anemia status (OR: 2.111; CI: 1.053-4.233; p: 0.035), history of maternal disease (OR: 2.514; CI: 1.260-5.015; p: 0.009) and HR (OR: 2.121; CI: 1.062-4.237; p: 0,033). In the multivariate results, the dominant risk factor was a history of maternal disease followed by anemia status and HR. The tendency of mothers who have a history of disease will increase the risk of maternal death compared to mothers who do not have a history of the disease.